Development of WEB-FIST (STEM-Based Physics Web) to Train Students' Critical Thinking on the Topic of Parabolic Motion - Dyah Ayu Wulan Sari; Abd. Kholiq (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This research aims to describe the feasibility of Web-FIST media in terms of validity and effectiveness. the use of Web-FIST to practice students' critical thinking on the topic of parabolic motion. This study uses a research design model of Hannafin & Peck. The data collection technique used was the validity instrument, the pretest-posttest in the form of an essay, and the response questionnaire with the subject of 13 students of class X Mathematics and Natural Sciences in Senior High School in Tuban. The validity is reviewed based on the suitability of the following aspects:1) the web system, 2) the correctness of the content of the material, 3) the STEM approach, 4) critical thinking characteristics, 5) the material with the nature of physics, and 6) competency standards. While the effectiveness in terms of the results of critical thinking observations and student responses. Media validation was carried out by two media experts. Based on the data analysis that has been carried out, the results of the Web-FIST validity are 92.83% with a very valid classification (92.83%). The results of the effectiveness of using Web-FIST obtained an N-Gain of 0.6 with a moderate classification, while from the assessment of student responses an average value of 86% was obtained with a very effective classification. Based on the results of the data analysis, it can be concluded that the developed Web-FIST is suitable for use in the learning process and can train students' critical thinking about parabolic motion.